A STUDY OF PHONOLOGICAL SYSTEM OF MENTOK DIALECT OF BANGKA LANGUAGE IN PUSUK DISTRICT OF KELAPA WEST BANGKA REGION - Sari, Dewi Purnama; Syaputri, Komala Dwi (Jurnal Ilmiah Bina Bahasa, 2019)
Abstract: The phonological system is a language system used by a society to distinguish itself from other societies. Bangka language is part of Malay cluster. This paper was written to describe Bangka language phonological system in Mentok dialect used in Pusuk based on (1) vowels, (2) consonant system, (3) diphthong, (4) distributions of vowels, consonants, and diphthongs, and (5) phonemic principle. The method used in this research was qualitative method. The data in this study was 248 basic vocabularies of Swadesh-based UnCen-SIL Wordlist. The data was collected with basic technique ?conversation technique?, followed by ?noting and recording technique?. The finding of Bangka language phonological system in Mentok dialect used in Pusuk was 9 vowels, 19 consonants, and 4 diphthongs. The distributions of vowel and consonant were incomplete. There was an allophone found in the study.  Keywords: Phonology, Phonemes, Vowels, Consonants, Diphthongs. Abstrak : Sistem fonologi adalah sistem bahasa yang digunakan oleh suatu masyarakat untuk membedakan dirinya dari masyarakat lain. Bahasa Bangka adalah bagian dari gugus Melayu. Penelitian ini ditulis untuk menggambarkan sistem fonologis bahasa Bangka dalam dialek Mentok yang digunakan di Pusuk berdasarkan pada (1) vokal, (2) sistem konsonan, (3) diftong, (4) distribusi vokal, konsonan, dan diftong, dan (5) prinsip fonemik. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Data dalam penelitian ini adalah 248 kosakata dasar dari UnCen-SIL Wordlist yang berbasis di Swadesh. Data dikumpulkan dengan teknik dasar "teknik percakapan", diikuti oleh "teknik mencatat dan merekam". Temuan sistem fonologis bahasa Bangka dalam dialek Mentok yang digunakan di Pusuk adalah 9 vokal, 19 konsonan, dan 4 diftong. Distribusi vocal dan konsonan tidak lengkap. Ada alofon yang ditemukan dalam penelitian.   Kata kunci: Fonologi, Fonem, Vokal, Konsonan, Diftong